Clastic injectites, internal structures and flow regime during injection: The Sea Lion Injectite System, North Falkland Basin. Issue 2 (26th November 2019) - Dodd, Thomas J. H.; McCarthy, Dave J.; Clarke, Stuart M.
Abstract: This paper details and describes a suite of 143 sub‐seismic‐scale clastic injectites encountered within the early Cretaceous, early post‐rift of the deep‐lacustrine North Falkland Basin. The injectites, referred to here as the Sea Lion Injectite System, are encountered below, above and in between the hydrocarbon‐bearing, deep‐lacustrine turbidite sandstones of the Bleaker 30, Sea Lion North, Sea Lion, Casper and Beverley fans. Sedimentary structures are documented within the injectites including: planar laminations, mud‐clast imbrication and clast alignment. Clasts align along centimetre‐scale foresets formed through ripple‐scale bedform migration in a hydraulically‐open fracture. The style of flow within the injectite system is interpreted as initially through fluid turbulence during an open fracture phase, which was followed by a later stage where laminar flow dominated, most likely during the closing phase of the fracture system. The host rocks display evidence for ductile deformation, which along with ptygmatic folding of dykes and internally injected mud‐clasts, suggests a period of injection into relatively uncompacted sediments. Evidence for brittle fracturing, in the form of stepped margins may be indicative of a separate phase of emplacement into more‐compacted sediments. This variability in deformation styles is related to multi‐phased injection episodes into host strata at different stages of consolidation and lithification at shallow burial depths. Injectites have been identified in four stratigraphic groupings: above the Bleaker 30 Fan and within/above the Sea Lion North Fan; within the hydrocarbon‐bearing Sea Lion Fan; overlying the Sea Lion Fan; and above/below the hydrocarbon‐bearing Casper and Beverley fans. This spatial association with the hydrocarbon‐bearing fans of the North Falkland Basin is important, considering the ability of injectite networks to form effective fluid‐flow conduits in the subsurface. Consequently, the findings of this study will improve the characterization of sub‐seismic scale injectites (and therefore fluid conduits) within otherwise impermeable strata.